Messtechnische Analyse der Grundwasserwärmepumpenanlage in einem Büro- und Produktionsgebäude - Georg Häring; Christoph Trinkl; Wilfried Zörner (Hochschule Ingolstadt - University of Applied Sciences, 2011)
In order to demonstrate the potential of technical building equipment based on renewable energies in daily industrial operation as well as to generate planning information, the CENTRE OF EXCELLENCE FOR RENEWABLE ENERGY RESEARCH at Ingolstadt University of Applied Sciences (Germany) monitored an innovative multifunctional building. Thermal energy for heating of the building is provided by two groundwater-coupled heat pumps. They feed the thermo-active structure of the building as well as the surface heating installations. Cooling is also driven by groundwater. In this case, the heat is also dissipated by the building's thermo-active structure and surface heating installations. A very special feature of this building is its heating/cooling facade that combines the glazing function with heating and cooling through its piping-like structure. During the monitoring, all energy flows in the building itself, the weather data, as well as the room conditions in selected sections of the building, were measured. Considering the different climatic conditions, the performance of the heat pumps and the installed heating/cooling systems, especially the effect of the active façade were evaluated. The function of the installed heating systems, especially the active façade, was demonstrated and the performance of the system could be improved significantly. However, a number of drawbacks with regard to operation and controls had to be overcome and recommendations for action were made. – – In einer messtechnischen Untersuchung wurde vom Kompetenzfeld Erneuerbare Energien die Leistungsfähigkeit eines grundwassergespeisten Heiz- und Kühlsystems mit Wärmepumpen in einem Büro- und Produktionsgebäude analysiert und bewertet. Dazu wurde eine umfängliche energetische Bilanzierung von Gebäudetechnik und Gebäude vorgenommen. Innerhalb des mehrjährigen Untersuchungszeitraumes konnten umfangreiche Erkenntnisse über die Effizienz und Arbeitsweise der Heiz- und Kühlanlage gewonnen werden. Dabei wurden eine Reihe von Problemstellungen im realen Anlagenbetrieb identifiziert sowie das Gesamtsystem auf Basis der Messergebnisse optimiert. Um die praxisrelevanten Forschungsergebnisse in zukünftigen innovativen Gebäudetechnikkonzepten einfließen zu lassen wurden konkrete Handlungsempfehlungen für die Planungs-, die Inbetriebnahme- und Einregulierungsphase sowie für die Betriebsführung abgeleitet.
urn:nbn:de:bvb:573-373
Keywords: 650